Aplicación de estratégias mtacognitivas por estudiantes de práctica pre profesional de educación inicial de la Facultad de Ciencias de la Educación y Humanidades Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Villanueva Córdova, Bábara (2022)
The present investigation was carried out with the purpose of describing the level of application of metacognitive strategies by students of pre-professional practice of initial education of the Faculty of Education Sciences and Humanities at the National University of the Peruvian Amazon, Iquitos in 2021 and so initiate research in this area little studied in the region. The type of descriptive research was used, with a non-experimental, cross-sectional, field, and univariate design. The population and sample for the investigation consisted of 80 students of pre-professional practice. The technique for obtaining data was the survey and a questionnaire was applied as an instrument validated by the judgment of judges. The findings in relation to the purpose of the research show that the level of application of metacognitive strategies in students of pre-professional practice of initial education of the Faculty of Education Sciences and Humanities at the National University of the Peruvian Amazon is medium at 88.7 %, high at 10.0% high and low at 1.3%.